Aplikasi Zeolit Alam Aktif Wonosari Sebagai Adsorben Zat Warna Remazol Yellow Fg - Neni Damajanti; Anwar Ma’ruf; Hanafi Khafid Nugraha (UM Purwokerto Press, 2021)
Zeolite as an adsorbent has been widely used. Zeolite activation was carried out to increase the absorption. This study aimed to determine the characteristics of the active zeolite and apply it as an adsorbent. The activation process was carried out by adding acid and calcining at 4500C for 6 hours. Remazol Yellow FG is a dye that is widely used in the textile industry. In this study, the adsorption process was carried out on the Remazol Yellow FG solution, then analyzed the effect of changes in pH (5, 6, 7, 8, 9), contact time (30, 60, 90, 120, 150 minutes) and the concentration of Remazol Yellow FG solution ( 50, 100, 150, 200, 250 ppm) on the adsorption of Remazol Yellow FG dye. From the analysis of the sample solution of Remazol Yellow, the values of Ce and qe can be calculated. These values were then used to calculate KL and KF in the Langmuir adsorption isotherm and Freundlich adsorption isotherm models. From the experimental results, it could be seen that as the contact time increased, the adsorption capacity would be greater. However, when the zeolite was already in the saturated phase, the adsorption capacity would tend to decrease. In the Langmuir adsorption isotherm, the KL value was 0.0274 L/mg and in the Freundlich adsorption isotherm model, the KF value was 29.25 L/mg. Remazol Yellow FG adsorption tended to follow the Langmuir adsorption isotherm model with an R2 value of 0.998.